Customer Acceptance in Online Marketing Using Technology Acceptance Model. Study case: PT Rajawali Medika Mandiri - Nathan, Evan; Fachira, Ira (Journal of Business and Management, 2015)
Abstract.Selling medical equipment is difficult because its use is specific and thus customer needs to be well informed about this product. This make the market of this product is small. To face the problem, nowadays every Distributor Company needs to spend much money on sales department to selling the product. This also happens in PT Rajawali Medika Mandiri. PT Rajawali Medika Mandiri needs to make efficiency in the time in the convince doctors and purchasing staff to inform the specification of medical equipment and the advantages if they choose PT Rajawali Medika Mandiri’s products. Online website is one of alternative that will help PT Rajawali Medika Mandiri because internet users in Indonesia will growth and it will help provide information for both doctors and purchasing staff. However that will be some factors that can affect the usage of internet. For some people, internet is a new technology. So, PT Rajawali Medika Mandiri needs to know whether customers will use this technology before PT Rajawali Medika Mandiri develops the website. The purpose of this research is to explore whether online marketing can be used as part of sales efforts to inform potential customers about medical equipment. To be able to explore it, TAM is used to identify customers’ perception about online website and how it influence customers’ intention to use it. In using TAM, PT Rajawali Medika Mandiri use eCatalogue website from LKPP as the prototype. The respond of correspondent are good enough to use this as prototype to build PT Rajawali Medika Mandiri’s own website. But, they need to improve more to make the customer more comfort in using the website. Keywords: Marketing, Technology, Online Marketing, Technology Acceptance Model.